2019
DOI: 10.20944/preprints201911.0133.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hospital Malnutrition, A Call for Political Action: A Public Health and nutritionDay Perspective

Abstract: Disease related malnutrition (DRM) is prevalent in hospitals and is associated with increased care needs, prolonged hospital stay, delayed rehabilitation and death. Nutrition care process related activities such as screening, assessment and treatment has been advocated by scientific societies and patient organizations but implementation is variable. We analyzed the cross-sectional nutritionDay database for prevalence of nutrition risk factors, care processes and outcome for medical patients. In 59126 medical p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…Several other studies have confirmed the association between malnutrition and increased mortality rates 13,41–43 . Also, the Nutrition Day showed that largest association with hospital death was observed in patients with reduced mobility or those who were bedridden 44 …”
Section: Discussionmentioning
confidence: 82%
“…Several other studies have confirmed the association between malnutrition and increased mortality rates 13,41–43 . Also, the Nutrition Day showed that largest association with hospital death was observed in patients with reduced mobility or those who were bedridden 44 …”
Section: Discussionmentioning
confidence: 82%
“…However, in work conducted by Hiesmayr et al and Sauer et al, it was determined that malnourished patients, in general, had higher 30-day in-hospital mortality when compared with well-nourished patients. 3,10 Our study did not specifically track 30-day outcomes for patients, which might explain lack of similar mortality observance. In addition, patients in the aforementioned studies were not necessarily in the intensive care unit (ICU), which may suggest less aggressive management, hence leading to higher mortality, especially in those cases of supportive care only.…”
Section: Discussionmentioning
confidence: 90%
“…La DAE es una entidad multifactorial en la que se ha reconocido el papel de factores socioeconómicos y patológicos del paciente para su instauración y progresión (3) , pero también se debe tener presente la influencia de la práctica clínica deficiente de cuidado nutricional y conocimiento respecto a la importancia de la nutrición clínica, como se ha identificado en estudios anteriores (1,2,4) . Se ha observado que el proceso de cuidado nutricional es aplicado en menos del 50 % de los pacientes, de los cuales el 11,9 % es identificado con DAE y el 17,6 % es identificado con riesgo de DAE; en menos del 50 % se monitoriza la ingesta alimentaria (aunque haya antecedentes de disminución de esta y de pérdida de peso no intencional), en menos del 46 % hay intervención de personal de nutrición, y menos del 41 % de expedientes tienen datos de riesgo nutricional o DAE (5) .…”
Section: Introductionunclassified